The Role of Underlying Filters in the Study of Phonological Interference - Josipović, Višnja (Array, 1992)
Interference of Croatian in the pronunciation of English is looked at in the light of Filter Theory, proposed by Calabrese (1988). It is argued that the notions of Filter Theory are useful in accounting for several phenomena observed in English spoken with a Croatian accent. With reference to the features she finds in the Croatian-accented English of her subjects, the author argues for the introduction of yet another theoretical notion – the repair strategy of fusion.